“Penelusuran Konsep Berpakaian Orang Beriman dan Implikasinya dalam Gereja Masa Kini” - Lian Fitriani gulo; Etry Roulina Sinaga; Della Regina Siburian; Elma Nababan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Wearing clothing is crucial in the life of a believer because it not only fulfills physical needs but also demonstrates spiritual, moral, and Christian identity values. Modern fashion and cultural developments influence the way congregations choose their clothing, resulting in varying opinions regarding appropriate standards of dress for believers in their religious lives. This study aims to explore how believers choose their clothing based on biblical teachings and examine its impact on congregational life today. The method used was a qualitative study with a literature review approach, analyzing the Bible, theological books, and related scientific journals. This study shows that in the Bible, the concept of dress for believers emphasizes modesty, simplicity, humility, and respect for God, rather than solely physical appearance. In the current church context, these principles remain appropriate as guidelines for congregations in demonstrating their faith through appropriate and responsible dress. The church plays a crucial role in providing a balanced understanding of dress ethics so that biblical values ​​remain in place without neglecting cultural developments and social conditions. Thus, the way believers dress can be a means of shaping Christian character and bearing witness to their faith in society